2018
DOI: 10.15171/apb.2018.026
|View full text |Cite
|
Sign up to set email alerts
|

Porous Microparticles Containing Raloxifene Hydrochloride Tailored by Spray Freeze Drying for Solubility Enhancement

Abstract: Purpose: The goal of this study was to improve the solubility and dissolution behavior of Raloxifene Hydrochloride (RH) using Spray Freeze Drying (SFD) technique.Methods: For achieving this goal, series of samples containing RH with polyvinylpyrrolidone (PVP) or hydroxypropyl beta cyclodextrin (HPβCD) used as solubility enhancers were prepared and microparticles were formed via SFD. The resultant microparticles were physicochemically characterized. Morphology of the microparticles were observed using Scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, its therapeutic efficacy is limited because of its poor solubility [ 5 ]. Several methods, such as the preparation of liposomes and nanoparticles [ 6 , 7 ] and self-microemulsion, have been used to increase the solubility and dissolution rate of insoluble drugs [ 8 , 9 , 10 , 11 ]. Solid dispersion (SD) can also efficiently increase the dissolution rate and solubility of insoluble drugs by changing the size and dispersion within the carrier.…”
Section: Introductionmentioning
confidence: 99%
“…However, its therapeutic efficacy is limited because of its poor solubility [ 5 ]. Several methods, such as the preparation of liposomes and nanoparticles [ 6 , 7 ] and self-microemulsion, have been used to increase the solubility and dissolution rate of insoluble drugs [ 8 , 9 , 10 , 11 ]. Solid dispersion (SD) can also efficiently increase the dissolution rate and solubility of insoluble drugs by changing the size and dispersion within the carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Moghaddam et al improved the solubility and dissolution activity of the poorly water-soluble compound raloxifene hydrochloride (RH). Moghaddam et al utilized the spray freeze-drying (SFD) technique and used polyvinyl pyrrolidone or hydroxypropyl beta-cyclodextrin as coating products [5]. Nogueira et al showed that freeze-dried microencapsulated blackberry pulp powders displayed enhanced solubility in water, while the antioxidant ability of the blackberries improved in comparison to that of blank particles, indicating good potential as a medium to release bioactive compounds into feed [6].…”
Section: Introductionmentioning
confidence: 99%